Variations of monsoon systems during the Holocene in the IPSL model - (:unkn) unknown (My University, 2011)
Numerous climate indicators and modelling experiments show the influence of orbital parameters on past variations of Asian and African monsoons. In particular, the monsoon precipitation and circulation were amplified at the beginning of the Holocene, when the insolation received at the top of the atmosphere was maximum during boreal summer. This study analyses the variations of monsoons systems over the Sahel, India and East-Asia at the beginning of the Holocene (9.5 kyr BP) and at the Mid-Holocene (6 kyr BP) with the IPSL-CM4 coupled model. This work highlights the role of precession of equinoxes and the influence of several climate feedbacks in modifying the seasonality and the relative amplification of monsoon systems throughout the Holocene. The amplitude and the phase of the mechanisms by which monsoons respond to insolation changes vary over India and Africa. This thesis also discusses the possible role of teleconnections between monsoons and the mid-latitudes. Sensitivity experiments to the reminiscent ice sheet at the beginning of the Holocene and to the freshwater flux due to ice melting in the North Atlantic show different responses of the Asian and African systems to these forcings. To complement these experiments, the impact of freshwater flux in the North Atlantic on monsoon systems is compared for several past (Eemian, Last Glacial Maximum, Early Holocene, Mid-Holocene), present and future periods. The results of the modelling experiments at the Holocene and at the Last Glacial Maximum have been compared with paleoclimatic marine records in the Indian Ocean
Keywords: African Research